Pyocyanin-enhanced neutrophil extracellular trap formation requires the NADPH oxidase. - Balázs Rada; Meghan A Jendrysik; Lan Pang; Craig P Hayes; Dae-Goon Yoo; Jonathan J Park; Samuel M Moskowitz; Harry L Malech; Thomas L Leto (PLoS ONE)
Beyond intracellular killing, a novel neutrophil-based antimicrobial mechanism has been recently discovered: entrapment and killing by neutrophil extracellular traps (NETs). NETs consist of extruded nuclear DNA webs decorated with granule proteins. Although NET formation is an important innate immune mechanism, uncontrolled NET release damages host tissues and has been linked to several diseases including cystic fibrosis (CF). The major CF airway pathogen Pseudomonas aeruginosa establishes chronic infection. Pseudomonas imbedded within biofilms is protected against the immune system, but maintains chronic inflammation that worsens disease symptoms. Aberrant NET release from recruited neutrophils was found in CF, but the underlying mechanisms remain unclear. One of the most important Pseudomonas virulence factors is pyocyanin, a redox-active pigment that has been associated with diminished lung function in CF. Here we show that pyocyanin promotes NET formation in a time- and dose-dependent manner. Most CF Pseudomonas clinical isolates tested produce pyocyanin in vitro. Pyocyanin-derived reactive oxygen species are required for its NET release. Inhibitor experiments demonstrated involvement of Jun N-terminal Kinase (JNK) and phosphatidylinositol 3-Kinase (PI3K) in pyocyanin-induced NET formation. Pyocyanin-induced NETs also require the NADPH oxidase because NET release in chronic granulomatous disease neutrophils was greatly reduced. Comparison of neutrophils from gp91phox- and p47phox-deficient patients revealed that pyocyanin-triggered NET formation is proportional to their residual superoxide production. Our studies identify pyocyanin as the first secreted bacterial toxin that enhances NET formation. The involvement of NADPH oxidase in pyocyanin-induced NET formation represents a novel mechanism of pyocyanin toxicity.